Determinan Kepuasan Keuangan (Financial Satisfaction) Pengguna Fintech Shopeepay - Roviatul Maqiyah (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to obtain an empirical study of the factors that influence financial satisfaction of fintech shopeepay users. In this case, how much influence does financial behavior, financial knowledge, and financial attitudes have on financial satisfaction, and also financial behavior factors as a mediating variable. This research is a survey research. The population in this study were all Jambi University students who used the ShopeePay fintech facility with a research sample of 99 respondents. The research data collection technique was carried out through a questionnaire. The data obtained were analyzed using the PLS (analysis techniquePartial Least Square) through the SmartPLS 3 software. The results showed that financial behavior, financial knowledge, and financial attitudes have a significant positive effect on financial satisfaction, financial knowledge and financial attitudes through financial behavior variables also have a significant positive effect on financial satisfaction.